The Windeby puzzle : history and story - Lowry, Lois (Clarion Books, 2023)
Told in two voices, two outcasts in an Iron Age village befriend each other, as disabled, orphaned Varick helps Estrild achieve her dream of becoming the first female warrior. Inspired by the Windeby bog body.